Ion Complexes
By forming an ionic complex from lignin sulfonic acid, a cationic polymer, and cellulose, the issues of moisture absorption and poor shape retention in existing composite materials are addressed, resulting in a material with enhanced moisture resistance and shape retention for industrial applications.
Patent Information
- Application Number
- JP2021117411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-07-15
AI Technical Summary
Existing ionic composite materials face challenges with high humidity responsiveness, moisture absorption, and poor shape retention in water, limiting their industrial applications as molding materials.
A water-soluble or water-suspended ionic complex is formed by mixing a lignin sulfonic acid-based compound, a cationic polymer, and a cellulose-based substance, which can be molded into various shapes and exhibits excellent moisture resistance and shape retention.
The resulting ionic complex demonstrates improved moisture resistance and shape retention, making it suitable for industrial use as a molding material.
Smart Images

Figure 0007662443000001 
Figure 0007662443000002 
Figure 0007662443000003
Abstract
Description
[Technical field]
[0001] The present invention relates to ionic complexes. [Background technology]
[0002] For the purpose of effective utilization of plant biomass, attempts have been made widely to utilize lignin or its derivatives, which are one of the main components constituting a plant body, as a moldable material. Lignosulfonic acid is a lignin-derived compound that can be obtained during pulp production by the sulfite method or by sulfuric acid treatment of lignin, and attempts have been made to utilize it as a moldable material like lignin. Lignosulfonic acid is an anionic polymer having many sulfo groups, which are anionic functional groups, in the molecule, and has high hydrophilicity. In general, as a method for utilizing such ionic polymers as materials, various anionic polymers and cationic polymers are combined to form ionic complexes, and various materials are prepared according to the properties of the obtained complexes.
[0003] Regarding the combination of lignin sulfonic acid and cationic polymers, Patent Document 1 describes an ionic composite material that has moldability, flexibility, elasticity, and self-repairing ability by combining lignin sulfonic acid with a cationic polymer. Patent Document 2 describes an ionic composite clay composition consisting of lignin sulfonic acid, which is a cation exchange type (i.e., anionic) polymer, and an anion exchange type (i.e., cationic) clay mineral. Patent Document 3 describes that a composition consisting of an aqueous cellulose furnish containing a high molecular weight cationic polymer and modified lignin can provide paper with improved drainage, retention, and formation. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-112526 A [Patent Document 2] JP 2006-133299 A [Patent Document 3] Japanese Patent Application Publication No. 7-173790 Summary of the Invention [Problem to be solved by the invention]
[0005] The ion composite material of Patent Document 1 can form a complex in an aqueous system, but the dried molded body has a problem that it is highly responsive to humidity, absorbs moisture in the air, and dissolves easily in water, making it difficult to use it industrially as a molding material. The ion composite clay composition of Patent Document 2 can form a molded body and has excellent shape retention in water, but the molded body has poor flexibility and contains solvents such as PEG400, which poses safety issues. The technology of Patent Document 3 is a technology that adds a high molecular weight cationic polymer and modified lignin to an aqueous cellulose paper furnish to improve paper quality, and is not related to applications other than paper.
[0006] An object of the present invention is to provide an ion complex which has excellent moisture resistance and shape retention and is composed mainly of a biomass component, which is a recyclable resource. [Means for solving the problem]
[0007] The present inventors have found that a water-soluble or water-suspendable ion complex formed by mixing a composition comprising a lignin sulfonate compound, a cationic polymer, and a cellulose-based substance in a solvent can be molded into various shapes and has moisture resistance and shape retention. Specifically, the present inventors have found that a water-soluble or water-suspendable ion complex of these polymers can be formed by combining a lignin sulfonate compound such as sodium lignin sulfonate with a cationic polymer and a cellulose-based substance, and that a sheet-shaped or three-dimensional complex can be easily obtained by drying the complex on a flat plate such as a petri dish and removing the solvent, and that the complex has excellent moisture resistance and shape retention in water. The present invention has been made based on these findings by the present inventors.
[0008] That is, the present invention provides the following [1] to [9]. [1] Component (A): a lignin sulfonic acid compound having a weight average molecular weight of 7,000 or more; Component (B): a cationic polymer, and Component (C): Cellulosic material is formed from The content of component (A) is 5 to 70% by weight based on the solid content weight of the ion complex. Ionic complexes. [2] Ingredients ( C The ion complex according to [1], wherein the ion complex comprises cellulose powder. [3] The ion complex according to [2], wherein the average particle size of the cellulose powder is 20 to 100 μm. [4] Ingredients ( C The ionic complex according to any one of [1] to [3], wherein the ionic complex comprises carboxymethylcellulose or a salt thereof. [5] The ionic complex according to [4], wherein the degree of etherification of the carboxymethyl cellulose or a salt thereof is 0.1 or more and 1.8 or less. [6] Component (A): a lignin sulfonic acid compound having a weight average molecular weight of 7,000 or more; Component (B): a cationic polymer, and Component (C): Cellulosic material in the presence of a solvent to prepare a solution or suspension of components (A) to (C). [7] The method according to [6], wherein components (A) and (B) are mixed in the presence of a solvent, and then component (C) is mixed therewith. [8] The method according to [6], wherein components (A) and (C) are mixed in the presence of a solvent, and then component (B) is mixed therewith. [9] The method according to any one of [6] to [8], further comprising removing the solvent from the solution or suspension of components (A) to (C). Effect of the Invention
[0009] According to the present invention, there are provided an ion complex which is formed from a lignin sulfonic acid compound, a cationic polymer, and a cellulose-based substance and which exhibits moisture resistance and shape retention, and a method for easily and quickly producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [1. Ion complex] The ionic complex is formed from components (A) to (C).
[0011] [Component (A): Lignosulfonic acid compound] Component (A) is a lignin sulfonic acid compound.
[0012] -Definition of lignosulfonic acid compounds- In this specification, the lignin sulfonic acid compound refers to a compound having a skeleton in which the carbon at the α-position of the side chain of the hydroxyphenylpropane structure of lignin is cleaved to introduce a sulfo group, or a modified product or salt thereof. The structure of the skeleton portion is shown in formula (1).
[0013] [ka] (1)
[0014] It is difficult to uniformly specify the chemical structure of lignosulfonic acid compounds by a general formula or the like, because lignin, which is the skeleton of lignosulfonic acid compounds, has a very complex molecular structure.
[0015] -Modified lignosulfonic acid compounds- The modified product of the compound having the skeleton represented by the above formula (1) (hereinafter also referred to as "modified lignosulfonic acid compound") is a compound obtained by modifying the above compound. Modification methods include chemical modification methods such as hydrolysis, alkylation, alkoxylation, sulfonation, sulfonate esterification, sulfomethylation, aminomethylation, desulfonation, and polyethylene glycolation; and a method of molecular weight fractionation of the lignosulfonic acid compound by ultrafiltration. Among these, chemical modification methods are preferred, and one or more reactions selected from the group consisting of hydrolysis, alkoxylation, desulfonation, alkylation, and polyethylene glycolation are preferred.
[0016] -Lignosulfonic acid compound salt- When the lignosulfonic acid compound is in the form of a salt, examples of the salt include monovalent metal salts, divalent metal salts, ammonium salts, and organic ammonium salts. Among these, calcium salts, magnesium salts, sodium salts, and mixed calcium-sodium salts are preferred.
[0017] -Method of manufacturing lignosulfonic acid compounds- The method of producing the lignosulfonic acid compound and its origin are not particularly limited, and it may be either a natural product or a synthetic product. The lignosulfonic acid compound is one of the main components of the waste liquor of sulfite pulp obtained by cooking wood under acidic conditions. Therefore, the lignosulfonic acid compound derived from the sulfite pulp waste liquor may be used.
[0018] -Method of manufacturing lignosulfonic acid compounds- Lignin sulfonic acid compounds (e.g., modified lignin sulfonic acid compounds) are abundantly contained in commercially available products, and such commercially available products may be used as component (A). Examples of commercially available products include Vanilex HW (manufactured by Nippon Paper Industries Co., Ltd.), Sunex M (manufactured by Nippon Paper Industries Co., Ltd.), Pearlex NP (manufactured by Nippon Paper Industries Co., Ltd.), and Sunflow RH (manufactured by Nippon Paper Industries Co., Ltd.).
[0019] --Weight-average molecular weight of lignosulfonic acid compounds-- The weight-average molecular weight of the lignin sulfonic acid compound is preferably 7,000 or more, more preferably 10,000 or more. This allows for good complexation with component (B) and a uniform ionic complex to be obtained. The upper limit is preferably 300,000 or less, more preferably 100,000 or less, and even more preferably 80,000 or less. This allows for an ionic complex with good shape retention to be obtained. Therefore, the weight-average molecular weight is preferably 7,000 to 300,000, more preferably 10,000 to 100,000, and even more preferably 10,000 to 80,000.
[0020] In this specification, the weight average molecular weight can be measured by a known method using gel permeation chromatography (GPC) in terms of polyethylene glycol. The measurement conditions for GPC are not particularly limited, but the following conditions can be exemplified. Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh or GL Science) Detector: Differential refractometer (manufactured by Tosoh)
[0021] Component (A) may be one type of lignin sulfonic acid compound, or a combination of two or more types differing in molecular weight, production method, origin, and the like.
[0022] -Content of component (A)- The content of component (A) is not particularly limited, and may be appropriately adjusted depending on the composition, type, and amount of the ionic complex. For example, the content is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the total amount of components (A) to (C). This can improve the shape retention of the ionic complex. The upper limit is preferably 70% by mass or less, and more preferably 60% by mass or less. This can improve the moisture resistance of the ionic complex. Therefore, the content of component (A) is preferably 5 to 70% by weight, more preferably 10 to 60% by weight, and even more preferably 20 to 60% by weight.
[0023] [Component (B): Cationic polymer] Component (B) is a cationic polymer. Examples of cationic polymers include polymers having a plurality of functional groups, at least one of primary, secondary, and tertiary amino groups, quaternary ammonium groups, and imino groups. Polymers made of a single monomer having at least one functional group, at least one of primary, secondary, and tertiary amino groups, quaternary ammonium groups, and imino groups, are preferred. Specific examples of such cationic polymers include poly(ethyleneimine), poly(allylamine), poly(diallyldimethylammonium chloride), chitosan, cationized cellulose, cationized carboxymethylcellulose, cationized starch, cationized hyaluronic acid, cationized guar gum, α-polylysine, ε-polylysine, α-polyornithine, δ-polyornithine, lysine-containing protein, poly(vinylpyridine), poly(vinyl N-methylpyridine), poly{[3-(methacryloylamino)propyl]tetrahydrofuran, poly(vinyl N-methylpyridine), ... trimethylammonium}, poly[(3-acrylamidopropyl)trimethylammonium], poly{[2-(methacryloyloxy)ethyl]trimethylammonium}, poly{[2-(acryloyloxy)ethyl]trimethylammonium}; cationic polymers in which the primary, secondary, and tertiary amino groups are converted to quaternary ammonium; compounds having imino groups such as polyarginine, poly(hexamethylene biguanide), polyhexamethylene guanidine, cyanophycin, and arginine-containing proteins; and salts thereof. When the cationic polymer is in the form of a salt, examples of the salt include inorganic acid salts such as hydrochlorides and organic acid salts such as acetates, from the viewpoint of imparting water solubility.
[0024] - Weight average molecular weight of cationic polymer - The weight average molecular weight of the cationic polymer is preferably 50,000 or more, more preferably 100,000 or more, and even more preferably 150,000 or more. The upper limit is preferably 500,000 or less, more preferably 450,000 or less, and even more preferably 400,000 or less. Therefore, it is preferably 50,000 to 500,000, more preferably 100,000 to 450,000, and even more preferably 150,000 to 400,000.
[0025] The component (B) may be one type of cationic polymer, or a combination of two or more types differing in molecular weight, structure, etc.
[0026] -Content of component (B)- The content of component (B) is not particularly limited, and may be appropriately adjusted depending on the composition, type, and amount of the ionic complex. For example, it is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the total amount of components (A) to (C). This can improve the shape retention of the ionic complex. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. This can improve the moisture resistance of the ionic complex. Therefore, the content of component (B) is preferably 5 to 70% by weight, more preferably 10 to 60% by weight, and even more preferably 20 to 50% by weight.
[0027] [Component (C): Cellulosic material] Component (C) is a cellulose-based material. Examples of the cellulose-based material include cellulose (natural cellulose, regenerated cellulose); cellulose derivatives such as carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, and methylcellulose; and salts thereof. The cellulose-based material may be a material containing one or more selected from cellulose and cellulose derivatives. The cellulose-based material is usually fibrous or powdery, and can be obtained from plants. Examples of the cellulose-based material include wood-based cellulose materials (e.g., wood flour, wood pulp); cotton-based cellulose materials (e.g., cotton, linter fiber); and processed or refined products thereof (e.g., cellulose powder, cellulose nanofiber, chemically modified cellulose nanofiber, carboxymethylcellulose). Examples of the cellulose-based material include wood pulp, cellulose powder, carboxymethylcellulose, and hydroxypropylmethylcellulose, and more preferably cellulose powder and carboxymethylcellulose.
[0028] -Cellulose powder- Cellulose powder is usually obtained by decomposing a plant raw material (e.g., wood pulp). Examples of the decomposition method include depolymerization (e.g., partial depolymerization by acid hydrolysis) using an acid (e.g., a mineral acid such as hydrochloric acid, sulfuric acid, or nitric acid), mechanical pulverization, or a combination thereof, and a method including at least mechanical pulverization is preferred. Mechanical pulverization can be carried out using a machine such as a pulverizer. Examples of the pulverizer include a cutting mill, a hammer mill, an impact mill, an airflow mill, and a vertical roller mill. When depolymerization using an acid is carried out before mechanical pulverization, it is preferable to carry out pretreatment such as neutralization, washing, deliquor, and drying. When using the mixing method 2 described later as a method for producing the composite, it is preferable to use a cellulose powder produced by mechanical pulverization without acid decomposition, which can prevent a decrease in the reinforcing effect caused by the elution of cellulose decomposition products even under highly alkaline conditions.
[0029] The average particle size of the cellulose powder is preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 30 μm or more. This makes it possible to suppress scattering and improve mixability when the cellulose powder is added to a reaction system. The upper limit is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. This makes it possible to maintain the kneadability during the formation of the ion complex and the smoothness of the resulting ion complex. Therefore, the average particle size of the cellulose powder is preferably 20 to 100 μm, more preferably 25 to 80 μm, and even more preferably 30 to 60 μm.
[0030] In this specification, the average particle size is the particle size when the volume accumulation distribution is 50%. The volume accumulation distribution can be obtained by a laser scattering method. The measuring device and measuring conditions are as follows. Measurement equipment: Laser diffraction particle size distribution measurement equipment (Mastersizer 3000, Spectris, Inc., Malvern Panalytical Division) Measurement conditions: Add a sample to the measurement section in water stirred at 3500 rpm so that the scattering intensity is about 10%, and measure under the following conditions. Analysis: General Purpose Analysis Sensitivity: Emphasis Light scattering model: Mie theory
[0031] The apparent specific gravity of the cellulose powder is preferably 0.1 g / ml or more, more preferably 0.15 g / ml or more. This can suppress the deterioration of workability due to scattering when the cellulose powder is added to the reaction system. The upper limit is preferably 0.6 g / ml or less, more preferably 0.45 g / ml or less, and even more preferably 0.4 g / ml or less. This can suppress the deterioration of dispersibility due to the occurrence of precipitation when the cellulose powder is added to the reaction system. Therefore, the range of 0.1 to 0.6 g / ml is preferable, the range of 0.1 to 0.45 g / ml is more preferable, and the range of 0.15 to 0.4 g / ml is even more preferable.
[0032] In this specification, the apparent specific gravity is the mass of cellulose powder per unit volume (1 mL). The apparent specific gravity can be measured, for example, by putting a sample (e.g., 10 g) into a measuring cylinder (e.g., 100 mL capacity), tapping the bottom of the measuring cylinder until the height of the sample stops decreasing, measuring the volume by reading the scale on the flattened surface, and dividing the weight of the sample by the volume.
[0033] The cellulose powder may be one that complies with the standards for "crystalline cellulose" and "powdered cellulose" in the 17th Revised Japanese Pharmacopoeia, "crystalline cellulose" in the standards for raw materials for quasi-drugs, and "microcrystalline cellulose" in the Official Specification of Food Additives.
[0034] -Carboxymethylcellulose or its salts- Carboxymethyl cellulose or a salt thereof is usually obtained by carboxymethylating a cellulose raw material such as wood pulp. The carboxymethylation is usually carried out by treating the cellulose raw material with a mercerizing agent (e.g., an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide) to prepare mercerized cellulose (alkali cellulose), and then adding an etherifying agent (e.g., monochloroacetic acid) to carry out an etherification reaction.
[0035] -Degree of etherification- The degree of etherification (degree of carboxymethyl substitution: DS) of carboxymethyl cellulose or a salt thereof is preferably 0.1 or more, more preferably 0.2 or more. This can improve the shape retention when the ionic complex (dried) is immersed in water. The upper limit is preferably 1.8 or less, more preferably 1.6 or less, and even more preferably 1.5 or less. This can suppress the ionic interaction with the cationic polymer within an appropriate range, and can improve the kneadability when forming the ionic complex. Therefore, the DS of carboxymethyl cellulose or a salt thereof is preferably 0.1 to 1.8, more preferably 0.1 to 1.6, and even more preferably 0.2 to 1.5. This can improve the mixability of carboxymethyl cellulose or a salt thereof when preparing the ionic complex, and the shape retention of the ionic complex.
[0036] In this specification, DS represents the degree of etherification per 6 carbon atoms in cellulose (mol / C6), and represents the number of carboxy groups per cellulose. DS can be confirmed by measuring the amount of base such as sodium hydroxide required to neutralize carboxymethylcellulose in a sample. In this case, when the carboxymethyl ether group of carboxymethylcellulose or a salt thereof is in the form of a salt, it is converted to carboxymethylcellulose in advance before measurement. When measuring, a base, back titration using an acid, and an indicator such as phenolphthalein can be appropriately combined.
[0037] The carboxymethyl cellulose or a salt thereof preferably has a viscosity of 1 to 10,000 mPa·s, more preferably 5 to 8,000 mPa·s, and even more preferably 5 to 5,000 mPa·s, in a 1% by mass aqueous solution measured with a Brookfield viscometer (30 rpm) at 25° C. When the viscosity is within the above range, it is easy to exert the effects of the present invention while preventing an extreme increase in viscosity in the ion complex.
[0038] The viscosity can be measured, for example, by preparing a 1% by mass aqueous solution of carboxymethylcellulose or a salt thereof and measuring the viscosity at 25° C. using a Brookfield viscometer at a rotation speed of 30 rpm.
[0039] When carboxymethylcellulose is in the form of a salt, examples of the salt include inorganic salts such as sodium salts and calcium salts.
[0040] Carboxymethylcellulose or a salt thereof may be one that complies with the standards for "carmellose," "carmellose sodium," "carmellose calcium," or "croscarmellose sodium" in the 17th Edition of the Japanese Pharmacopoeia, "carboxymethylcellulose sodium" and "dried carboxymethylcellulose sodium" in the Standards for Quasi-Drug Ingredients, or "carboxymethylcellulose calcium" and "carboxymethylcellulose sodium" in the Official Specification for Food Additives.
[0041] The component (C) may be one type of cellulosic material, or a mixture of two or more types differing in molecular weight, structure, etc.
[0042] -Content of component (C)- The content of component (C) is not particularly limited, and may be appropriately adjusted depending on the composition, type, and amount of the ionic complex. For example, it is preferably 1% by weight or more, more preferably 5% by weight or more, and even more preferably 10% by weight or more. This can improve the moisture resistance of the ionic complex. The upper limit is preferably 80% by weight or less, more preferably 60% by weight or less, and even more preferably 40% by weight or less. When the content of component (C) is 80% by weight or less, the shape retention of the ionic complex is good, and the surface hardness can be increased. Therefore, the content of component (C) is preferably 1 to 80% by weight, more preferably 5 to 60% by weight, and even more preferably 10 to 40% by weight, relative to 100% by weight of the ionic complex.
[0043] [Optional ingredients] The ionic complex may contain optional components other than the components (A) to (C) as necessary, such as antioxidants, preservatives, stabilizers, and solvents.
[0044] -solvent- Examples of the solvent include water, and organic solvents that can be dissolved in water, such as methanol, ethanol, isopropyl alcohol, ethylene glycol, glycerin, polyethylene glycol, formic acid, acetic acid, propionic acid, acetone, acetonitrile, tetrahydrofuran, dimethylsulfoxide, dimethylformamide, and dioxane, and may be mixed solvents of two or more kinds. Among these, water is preferable from the viewpoint of safety.
[0045] [Morphology of ionic complexes] The ionic complex may be formed from components (A) to (C). Its form may be, for example, a form in which the components are bonded by ionic bonds, hydrogen bonds, or the like, or a form in which the components are not bonded.
[0046] The ionic complex may be in a state where it is dissolved or suspended (dispersed) in a solvent (eg, water) (liquid state), or it may be in a state where it is substantially free of solvent (solid state).
[0047] 2. Preparation of ion complex The ionic complex is preferably produced by a method including a step of mixing the components (A) to (C) in the presence of a solvent (mixing step).
[0048] -Mixing process- The mixing step may be carried out by adding the components (A) to (C) and the solvent all at once or sequentially into the system, and is preferably carried out by adding them sequentially into the system. As the order of addition of the components (A) to (C), for example, a method of adding and mixing the components (A) and (B) and then adding and mixing (C) (mixing method 1) or a method of adding and mixing the components (A) and (C) and then adding and mixing (B) (mixing method 2) is preferable. This allows the components (A) to (C) to be mixed uniformly, and the surface strength of the ion complex can be improved. Among them, mixing method 2 is more preferable because it allows the component (C), which has a higher water absorption, to be mixed more uniformly with the components (A) and (B).
[0049] The mixing is usually carried out in the presence of a solvent. The solvent is the same as the specific example and preferred example of the solvent as the component of the ion complex. The order of adding the solvent is not particularly limited, and may be before, during, or after the addition of the components (A) to (C). However, it is preferable to mix at least one of the components (A) to (C) (preferably components (A) and (B)) in advance with the solvent to prepare a solution or suspension, and add it to the system as a solution or suspension. This allows for more uniform mixing. In particular, by mixing the components (A) and (B) in advance with the solvent, the ionic interaction can be increased. In the case of mixing method 1, it is preferable to mix each of the components (A) to (C) in advance with the solvent to prepare a solution or suspension, and add it to the system as a solution or suspension. In the case of mixing method 2, it is preferable to mix the components (A) and (B) in advance with the solvent to prepare a solution or suspension, and add it to the system as a solution or suspension. The weight ratio of components (A) to (C) and the solvent can be adjusted to a total of components (A) to (C):solvent=40:60 to 5 to 95. When components (A), (B), and (C) are added as a solution or suspension, the solid content concentration of each of components (A), (B), and (C) in the solution is preferably 5 to 40% by weight, more preferably 10 to 30% by weight. Mixing can be performed using a mixing device such as a planetary centrifugal mixer, a twin-screw extrusion kneader, or a line mixer. The mixing conditions are preferably performed until each component is uniformly mixed, and can be appropriately set depending on the device used.
[0050] -Solvent removal process- The mixture obtained by the mixing step may be used as an ion complex as it is, but after mixing, if necessary, a step of removing the solvent from the prepared solution or suspension (solvent removal step) may be performed, and the resultant product after the treatment may be used as an ion complex. Examples of the removal of the solvent include drying (e.g., freeze drying, heat drying, spray drying) and solid-liquid separation (e.g., precipitation treatment). For example, when removing water as a solvent by heat drying, the drying temperature is preferably low, and more preferably 60°C or less, 55°C or less, 50°C or less, or 45°C or less. The drying time is usually 12 hours or more, preferably 15 hours or more, more preferably 20 hours or more, and even more preferably 24 hours or more. Note that, before the drying treatment, a step of removing water as a solvent may be performed by putting the aqueous solution or suspension into an organic solvent and collecting the precipitate. The solvent is preferably removed until the solvent content in the ionic complex obtained after the treatment is, for example, 20% by weight or less, preferably 18% by weight or less, with the lower limit being, for example, 1% by weight or more, preferably 3% by weight or more. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the spirit of the above and below descriptions, all of which are included in the technical scope of the present invention. In the examples, unless otherwise specified, "%" means % by weight, and "parts" means parts by weight. Furthermore, the measurement methods for physical properties, etc. are the same as those described above, unless otherwise specified.
[0052] [Materials used] (1) Component (A): Lignosulfonic acid compound Lignin 1: Sanex P252 (powder, sodium lignosulfonate, weight average molecular weight 12,300, manufactured by Nippon Paper Industries Co., Ltd.) Lignin 2: Sanex P321 (powder, magnesium lignosulfonate, weight average molecular weight 11,700, manufactured by Nippon Paper Industries Co., Ltd.) Lignin 3: Pearlex NP (powder, high-purity sodium lignosulfonate, weight-average molecular weight 16,100, manufactured by Nippon Paper Industries Co., Ltd.) Lignin 4: Reagent lignosulfonic acid sodium salt (powder, lignosulfonic acid, weight average molecular weight 5,800, Merck)
[0053] (2) Component (B): Cationic polymer Cation 1: Poly(diallyldimethylammonium chloride) (20% aqueous solution, weight average molecular weight 200,000 to 350,000, Merck)
[0054] (3) Component (C): Cellulosic material Cellulose 1: KC Flock W-50GK (powder, cellulose powder, average particle size 45 μm, apparent specific gravity 0.24 g / ml, manufactured by Nippon Paper Industries Co., Ltd.) Cellulose 2: Sunrose F-30MC (powder, carboxymethyl cellulose, DS = 0.7, 250 to 350 (mPa·s 1%, 25°C), manufactured by Nippon Paper Industries Co., Ltd.) Cellulose 3: KC Flock W-100GK (powder, cellulose powder, average particle size 37 μm, apparent specific gravity 0.30 g / ml, manufactured by Nippon Paper Industries Co., Ltd.) Cellulose 4: Sunrose A20SH (powder, carboxymethyl cellulose, DS = 1.5, 150 to 250 (mPa·s 1%, 25°C), manufactured by Nippon Paper Industries Co., Ltd.) Cellulose 5: Sunrose SLD-F1 (powder, carboxymethyl cellulose, DS = 0.28, 10 to 200 (mPa·s 1%, 25°C), manufactured by Nippon Paper Industries Co., Ltd.) Cellulose 6: Sunrose F-350MC (powder, carboxymethyl cellulose, DS = 0.9, 2000 to 4000 (mPa·s 1%, 25°C), manufactured by Nippon Paper Industries Co., Ltd.)
[0055] [Measurement method] -Weight average molecular weight- The weight average molecular weight was measured by gel permeation chromatography (GPC) using polyethylene glycol as the conversion factor. The GPC measurement conditions were as follows: Measuring device: Tosoh Columns used: Shodex Column OH-pak SB-806HQ, SB-804HQ, SB-802.5HQ Eluent: 0.05 mM sodium nitrate / acetonitrile 8 / 2 (v / v) Standard material: Polyethylene glycol (Tosoh or GL Science) Detector: Differential refractometer (manufactured by Tosoh)
[0056] -Degree of etherification (DS)- Approximately 2.0 g of a carboxymethylcellulose sample was weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. 100 mL of nitric acid methanol (a solution of 100 mL of concentrated nitric acid added to 1000 mL of methanol) was added and shaken for 3 hours to convert carboxymethylcellulose salt (CMC salt) to H-CMC (carboxymethylcellulose). 1.5 to 2.0 g of bone-dried H-CMC was weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. The H-CMC was moistened with 15 mL of 80% methanol, 100 mL of 0.1 N NaOH was added, and the mixture was shaken at room temperature for 3 hours. Excess NaOH was back-titrated with 0.1 N H2SO4 using phenolphthalein as an indicator. DS was calculated using the following formula 1.
[0057] (Formula 1) A = [(100 x F - (0.1N H2SO4 (mL)) x F') x 0.1] / (bone dry weight of H-CMC (g)) Carboxymethyl substitution degree (CM-DS) = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1g of H-CMC (mL) F': Factor of 0.1N H2SO4 F: Factor of 0.1N NaOH
[0058] -viscosity- Carboxymethylcellulose or its salt is weighed into a 1000 mL glass beaker and dispersed in 900 mL of distilled water to prepare an aqueous dispersion with a solid content of 1% (w / v). The aqueous dispersion is stirred at 600 rpm for 3 hours at 25°C using a stirrer. The viscosity is then measured after 3 minutes using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) with a No. 1 rotor at 30 rpm in accordance with the method of JIS Z-8803.
[0059] -Average particle size- A laser diffraction particle size distribution analyzer (Mastersizer 3000, Malvern Panalytical Division, Spectris Co., Ltd.) was used. The measurement principle was laser scattering, and the sample was added to the measurement section in water stirred at 3500 rpm so that the scattering intensity was about 10%. Particle size distribution was measured by wet measurement. When the particle size distribution was expressed as a volume accumulation distribution, the value at which the integrated value of the volume accumulation distribution was 50% was taken as the average particle size. Analysis of particle size distribution was performed under the following conditions. Analysis: General purpose Analysis Sensitivity: Emphasis Light scattering model: Mie theory
[0060] -Apparent specific gravity- 10 g of sample was placed into a 100 mL graduated cylinder and the bottom of the graduated cylinder was tapped until the height of the sample no longer decreased. The scale on the flattened surface was then read to measure the volume per 10 g of sample, and the weight per unit volume (1 mL) was calculated to obtain the apparent specific gravity (g / mL).
[0061] [Examples 1 to 14 and Comparative Examples 1 to 7] Components (A) (lignin 1-4), component (B) (cation 1), and component (C) (cellulose 1-6) shown in Table 1 were mixed in the compounding ratios shown in Table 1 so that the total solid content was 10.0 g, and this mixture was transferred to a PFA tray (small tray S, manufactured by Sanplatec Co., Ltd.) and dried at a temperature of 40°C for 24 hours to obtain an ion complex. The solid content of the ion complex was 3-10 wt%. The ion complex was mixed by one of the following two methods, which are shown in Table 1.
[0062] Mixing method 1: Prepare a 20% aqueous solution of component (A), mix a 20% aqueous solution of component (A) with a 20% aqueous solution of component (B) in the mixing ratio shown in Table 1, and then add and mix a 20% aqueous solution of component (C) in the mixing ratio shown in Table 1. Mixing method 2: Prepare a 5% aqueous solution of component (A), mix the powdered component (C) with the 5% aqueous solution of component (A) in the mixing ratio shown in Table 1, and then add a 20% aqueous solution of component (B) in the mixing ratio shown in Table 1 and mix. For mixing, a planetary centrifugal mixer (Kurabo Industries, Ltd., Mazerustar: KK-250S) was used. That is, each sample was placed in a HDPE container and mixed under the conditions of revolution level 7, rotation level 7, and mixing time 120 seconds.
[0063] [Table 1]
[0064] [Notes to Table 1] The blend ratios in Table 1 are the blending rates (%) of solids relative to the total solids.
[0065] (Evaluation of shape retention) The shape retention of the samples obtained in each Example and Comparative Example was evaluated. 10.0 g of the ion complex obtained in each Example was added to 100 g of water, and the solubility after standing was confirmed. If it completely dissolved within 1 hour, it was rated as "instantly dissolved", if it dissolved within 7 days, it was rated as "gradually dissolved", if it did not dissolve even after 7 days, it was rated as "not dissolved", and if it did not dissolve even after 7 days and did not swell due to water absorption, it was rated as "not dissolved and no swelling". The results are shown in Table 2.
[0066] (Evaluation of moisture resistance) The moisture resistance of the samples obtained in each Example and Comparative Example was evaluated. 10.0 g of the ion complex obtained in each Example was left for 7 days in an environment with a temperature of 20° C. and a relative humidity of 50%. The weight increase rate (%) of the ion complex after leaving for 7 days relative to the weight at the start of drying was taken as the moisture absorption rate. In addition, the surface properties of the ion complex after leaving for 7 days were evaluated as "sticky" if the ion complex adhered to the finger, "slightly sticky" if the ion complex did not adhere to the finger but the surface was viscous, and "not sticky" if nothing adhered to the finger and the surface was not viscous. Furthermore, the surface hardness of the ion complex after leaving for 7 days was measured using a Yamanaka soil hardness tester (standard type, manufactured by Fujiwara Seisakusho). If the ion complex broke during the surface hardness measurement, the value at which it broke was taken as the surface hardness. The results are shown in Table 2.
[0067] [Table 2]
[0068] The ionic complexes of Comparative Examples 1 to 3, which did not contain a cellulosic material, were dissolved in water, had insufficient shape retention, and absorbed moisture and became sticky in an environment of 50% relative humidity. Comparative Example 4, which did not contain component (B), Comparative Example 5, which contained 3% by weight or less of component (A), and Comparative Example 7, which did not contain components (A) and (B), had low moisture absorption and moisture resistance, but quickly dissolved in water and had poor shape retention. The ionic complex of Comparative Example 6, which used lignin sulfonic acid with a weight-average molecular weight of less than 7,000, was poor in shape retention and moisture resistance in water, and it was presumed that the complex of components (A) to (C) was insufficient.
[0069] In contrast, the ionic complexes described in Examples 1 to 14 did not dissolve in water and maintained their shape even after 7 days, demonstrating excellent shape retention in water. Furthermore, the ionic complexes of the Examples had a low moisture absorption rate (weight change rate) of 20% or less even when left to stand in an environment with a relative humidity of 50%, no or only suppressed stickiness in the surface properties, and a surface hardness of 50 kg / cm 2 As the results showed that the moisture resistance was excellent, the results were as follows: These results show that the present invention can provide an ion complex that is excellent in shape retention and moisture resistance and is suitable for industrial use.
Claims
1. Component (A): a lignin sulfonic acid compound having a weight average molecular weight of 7,000 or more; Component (B): a cationic polymer, and Component (C): Cellulosic material is formed from The content of component (A) relative to the solid content weight of the ion complex is 10 to 60% by weight, Component (C) contains a cellulose powder having an average particle size of 30 to 60 μm; Ionic complexes.
2. The ionic complex according to claim 1 , wherein the apparent specific gravity of the cellulose powder is 0.1 g / ml or more.
3. Component (A): a lignin sulfonic acid compound having a weight average molecular weight of 7,000 or more; Component (B): a cationic polymer, and Component (C): Cellulosic material is formed from The content of component (A) relative to the solid content weight of the ion complex is 10 to 60% by weight, Component (C) is an ionic complex containing carboxymethylcellulose or a salt thereof, the viscosity of a 1% by mass aqueous solution of which is 1 to 10,000 mPa·s as measured at 25° C. using a Brookfield viscometer (30 rpm).
4. The ionic complex according to claim 3, wherein the degree of etherification of the carboxymethyl cellulose or a salt thereof is 0.1 or more and 1.8 or less.
5. The ionic complex described in claim 3 or 4, wherein component (C) contains carboxymethylcellulose or a salt thereof, and the carboxymethylcellulose or the salt thereof has a viscosity of 5 to 8,000 mPa·s as a 1 mass % aqueous solution measured at 25°C using a B-type viscometer (30 rpm).
6. Component (A): a lignin sulfonic acid compound having a weight average molecular weight of 7,000 or more; Component (B): a cationic polymer, and Component (C): Cellulosic material of, In the presence of a solvent, components (A) and (B) are mixed together, and then component (C) is mixed therewith; or Components (A) and (C) are mixed in the presence of a solvent, and then component (B) is mixed therein; A method for producing an ionic complex comprising preparing a solution or suspension of components (A)-(C).
7. The method of claim 6 further comprising removing the solvent from the solution or suspension of components (A)-(C).
Citation Information
Patent Citations
Cellulosic, modified lignin and cationic polymer compositionand preparation of improved paper or paperboard
JP1995173790A
Ion compound type clay composition and solidified matter thereof
JP2006133299A
Agricultural liquid mulch composition
JP2018170998A
Method for producing soil solidification composition and soil solidification method using the same
JP2019056075A
Ion composite material containing lignin sulfonic acid and cationic polymer as components
JP2019112526A